Reconstruction of the Odontoid Process by a Tricortical Iliac Crest Graft in a Case of Tuberculosis of C1, C2, and C3 Vertebrae - Golwala, Paresh (Cureus, 2016)
Tuberculosis (TB) is an emerging disease which affects about one-third of the world’s population, especially in developing countries. TB of the spine is the most common type of skeletal TB. Cervical spine TB is rare, constituting 2-3% of all cases of spinal TB. We would like to present an unusual case of tuberculosis of the C1, C2, and C3 vertebrae with neurological deficit and its difficult management. A new method of treatment was done for this patient, which included reconstruction of the odontoid process using a tricortical iliac crest graft that was fixed with an anterior cervical plate. On follow-up, there was good incorporation of the graft. The neurological condition of the patient improved and was normal with partial restriction of neck movements. We suggest this technique to be worthwhile for treatment of this disease at this location.